منهج ابن عبد السلام الهواري في تقرير المصطلحات الفقهية من خلال مسائل الجهاد والنكاح في كتابه (تنبيه الطالب): Ibn 'Abd al-Salām al-Hawārī's Method of Interpreting Fiqh Terms on the Issue of Jihad and Marriage in His Book (Tanbīh Al-Ṭālib) - Tarek, Beche (البصيرة: مجلة الدراسات الإسلامية, 2024)
This research aims to explain the method of "Muhammad bin Abd al-Salām al-Hawārī" (d. 749) in assessing various problems in general and in terms of jurisprudence in the Maliki school of thought from the end of the book "Jihad" to the beginning of the chapter on marriage disgrace in general. special. This research uses an inductive-deductive approach to the words of Ibn 'Abd al-Salām, especially in the part studied. This research found several findings, the most important of which is that Ibn 'Abd al-Salām al-Hawārī's method in interpreting the term Fiqh on the issue of jihad and marriage shows the author's scientific position. This can be seen in the clarity of his expressions, the ease of his words, his ability to present postulates and explain debates on fiqh issues through diversity in terms of postulates based on postulates for various purposes, whether for linguistic issues or explaining the causes of disagreements among ulama, or mentarjih, or establishing jurisprudence laws, and their additions to Islamic jurisprudence through narrations and various methods, and opinions in the Maliki school of thought, in addition to other schools of jurisprudence. Apart from that, it shows his attention to the propositions, which can be seen from his persistence in drawing the propositions from the Qur'an, Sunnah, ijma' and kias. Likewise, one of its features is that its method mentions the assessment of hadith except for certain cases, considering the frequent use of fiqh terms, both related to the title of the imam and the book.